Antibacterial properties of alafosfalin combined with cephalexin. - Atherton, F R (1981)
The phosphonopeptide alafosfalin (L-alanyl-L-1-aminoethylphosphonic acid) exhibited synergy in vitro and in animal studies against a range of bacterial genera when combined with cephalexin. Alafosfalin also showed synergy with mecillinam and, to a much lesser extent, with ampicillin. Synergy with cephalexin was more pronounced when the bacteria were relatively insensitive to the beta-lactam component. The action of this combination involved both an inhibitory and a bacteriolytic mechanism which was abolished by concurrent treatment with the aminopeptidase inhibitor, bestatin. Regrowth of subpopulation resistant to either component was markedly reduced by the combination. The potential of alafosfalin combined with cephalexin for use in therapy is discussed.